VD_FINDINFO HC / 2025 / 279 vom 24. Januar 2025 - VD Tribunal cantonal (2025)
COMPÉTENCE, COMPÉTENCE RATIONE MATERIAE, INTÉRÊT DE FAIT, INTÉRÊT ÉCONOMIQUE | 113 al. 1 LOJV, 113 LOJV, 92 al. 2 CPC (CH)